2021
DOI: 10.1161/jaha.120.018370
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine‐Associated Heart Failure Hospitalizations Across the United States: Geographic and Social Disparities

Abstract: Background Although methamphetamine abuse is associated with the development of heart failure (HF), nationwide data on methamphetamine‐associated HF (MethHF) hospitalizations are limited. This study evaluates nationwide HF hospitalizations associated with substance abuse to better understand MethHF prevalence trends and the clinical characteristics of those patients. Methods and Results This cross‐sectional period‐prevalence study used ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
2
28
0
1
Order By: Relevance
“…A 9.5% association of adverse effects due to cardiovascular disorders was reported by a multicenter study published in 2011 in cannabis-related hospital admissions [6]. The U.S. National Vital Statistics for 1990-2014 data demonstrated that mortality rates in states where marijuana is legal showed a 2.3% and 1.3% increase in cardiac mortality among men and women, respectively, compared to states where marijuana is not legal [6]. The association between the development of heart failure or exacerbation and marijuana use has not been fully demonstrated [6].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…A 9.5% association of adverse effects due to cardiovascular disorders was reported by a multicenter study published in 2011 in cannabis-related hospital admissions [6]. The U.S. National Vital Statistics for 1990-2014 data demonstrated that mortality rates in states where marijuana is legal showed a 2.3% and 1.3% increase in cardiac mortality among men and women, respectively, compared to states where marijuana is not legal [6]. The association between the development of heart failure or exacerbation and marijuana use has not been fully demonstrated [6].…”
Section: Introductionmentioning
confidence: 91%
“…There are mixed findings in the literature when evaluating the cardiovascular effects of cannabis use. A 9.5% association of adverse effects due to cardiovascular disorders was reported by a multicenter study published in 2011 in cannabis-related hospital admissions [6]. The U.S. National Vital Statistics for 1990-2014 data demonstrated that mortality rates in states where marijuana is legal showed a 2.3% and 1.3% increase in cardiac mortality among men and women, respectively, compared to states where marijuana is not legal [6].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, from 2010 to 2017 in Washington state in the Western USA, the age-adjusted rate for methamphetamine-involved hospitalizations increased from 6.3 to 8.5/100,000 [ 21 ]. Nationally, hospital admissions for heart failure involving methamphetamine increased from 547 in 2002 to 6625 in 2014 [ 22 ]. Among people seeking substance use disorder treatment for heroin, the proportion of patients reporting methamphetamine use increased nearly 500% between 2008 and 2017 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%